Prognostic value of the systemic immune-inflammation index in lung cancer patients receiving immune checkpoint inhibitors: A meta-analysis. - Yanhui Yang; Ji Li; Yi Wang; Lei Luo; Yi Yao; Xiaoyang Xie (PLoS ONE)
Purpose To explore the association between the systemic immune-inflammation index (SII) score and prognosis in immune checkpoint inhibitor (ICI)-treated patients with lung cancer. Methods PubMed, EMBASE, Web of Science, and CNKI databases were searched up to August 1, 2024. Progression-free survival (PFS) and overall survival (OS) were the primary outcomes queried. Hazard ratios (HRs) and 95% confidence intervals (CIs) were combined, and subgroup analysis was based on pathological type [non-small cell lung cancer (NSCLC) vs. small-cell lung cancer (SCLC)], lines of ICIs (first-line vs. second- or further-line), and combinations of other therapies (yes vs. no). Results Twenty retrospective studies with 2424 participants were included. The pooled results demonstrated that an elevated SII was associated with poorer PFS (HR = 1.82, 95% CI: 1.49-2.21; P < 0.001) and OS (HR = 2.31, 95% CI: 1.73-3.09; P < 0.001) in lung cancer patients receiving ICIs. Subgroup analysis stratified by pathological type, lines of ICIs and combinations of other therapies for PFS and OS further revealed the predictive role of the SII in ICI-treated lung cancer patients. Conclusion Based on current evidence the SII is significantly related to prognosis and could serve as a reliable prognostic indicator in lung cancer patients receiving ICIs.